ANALISIS YURIDIS PENYELESAIAN SENGKETA LESSOR DAN LESSE DALAM PEMBIAYAAN KONSUMEN KENDARAAN BERMOTOR TANPA JAMINAN FIDUSIA OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN - Nelvia Gusti Nola; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In civil case No. 239 / Pdt / SUS-BPSK / 2014 / PN.PBR. Lessee under the name HN and EM bought 2 units of Mitsubishi Fuso-FV419 J / Dump Truck vehicle through leasing services. The lessor is the PT. SMSF. But starting in April 2012, EM's efforts are declining. So EM suffered congestion in paying credit repayments starting from April 2012. So the leasing party to withdraw the vehicle that became the object of the agreement without notice.The type of this research is normative law with legal principles applied to the rule of law, which is benchmark to behave in using fiduciary guarantee, while if seen from its nature this research is descriptive. This study uses secondary data obtained through literature study.The results of this study are the authority of the Consumer Dispute Settlement Board to resolve disputes between lessors and lessees in consumer protection of motor vehicles without fiduciary guarantees with lessees named HN and EM who purchase 2 units of Mitsubishi Fuso-FV419 J / Dump Truck vehicles through leasing services, lessor is PT. SMSF and has withdrawn and auctioned the Mitsubishi Fuso-FV419 J / Dump Truck vehicle without the knowledge of the lessee is conducting the handling and settlement of consumer dispute, by means of mediation, conciliation or arbitration, providing consumer protection consultation, supervising the inclusion of the standard clause, reporting to the investigator general in the event of a violation, receiving written or unwritten complaints from the consumer about the occurrence of violation of consumer protection, conducting research and examination of consumer disputes, summoning business actors suspected of having violated consumer protection and calling and presenting witnesses, expert witnesses and / or any person deemed aware of infringement. Dispute settlements of lessors and lessees in consumer financing without fiduciary guarantees by the Consumer Dispute Settlement Bodies in providing protection to consumers based on established legal basis and by the principle of prioritizing deliberation, prompt, cheap and fair. Settlement of cases conducted by BPSK Pekanbaru city in the form of conciliation, mediation and abitrage.Keywords: lessor, lessee, unsecured fiduciary.